Adeno‐associated virus‐mediated over‐expression of CREB‐regulated transcription coactivator 1 in the hippocampal dentate gyrus ameliorates lipopolysaccharide‐induced depression‐like behaviour in mice. Issue 1 (5th March 2019) - Ni, Saiqi; Huang, Hua; He, Danni; Chen, Hang; Wang, Chuang; Zhao, Xin; Chen, Xiaowei; Cui, Wei; Zhou, Wenhua; Zhang, Junfang
Abstract: Depression is a highly complex global disabling psychiatric disorder. Unfortunately, the currently available antidepressants are not effective in a significant percentage of patients. Therefore, the underlying mechanisms of depression must be explored at the molecular level to discover new candidate molecular targets for depression treatment. Behavioural and molecular depression‐like endophenotypes have been observed in cyclic AMP response element‐binding protein‐regulated transcription coactivator 1 ( Crtc1 ) knockout mice; however, the underlying mechanism for these endophenotypes remains unclear. This work investigated the role of hippocampal CREB‐regulated transcription coactivator 1 (CRTC1) in depression using a recombinant adeno‐associated virus (AAV) system to alter Crtc1 gene expression and explore its potential mechanism. We found that shRNA‐mediated Crtc1 gene knockdown (AAV‐shCRTC1) in the dentate gyrus regions of the ventral hippocampus directly resulted in depression‐like behaviours and down‐regulation of brain‐derived neurotrophic factor and neuropeptide VGF levels. A widely used depression model induced by lipopolysaccharide administration (0.5 mg/kg, i.p.) was applied in our study and was validated by increased immobility time in the tail‐suspension and forced swim tests and decreased sucrose consumption in the sucrose preference test. Importantly, CRTC1 over‐expression mediated by AAV‐CRTC1 in the ventral dentate gyrus regions prevented lipopolysaccharide‐induced depressive‐like behaviours, the down‐regulation of brain‐derived neurotrophic factor and VGF, and the accumulation of pro‐inflammatory cytokines such as interleukin‐6, interleukin 1‐β and tumour necrosis factor α in mice. Together, our findings indicate that CRTC1 is a key factor in depression‐like behaviour and provide an important reference for finding a novel drug target in the neuroinflammatory and neurotrophic pathways for curing depressive disorders. Cover Image for this issue: doi: 10.1111/jnc.14500 . Abstract : CREB‐regulated transcription coactivator 1 (CRTC1) mainly expressed in the brain is required for CREB‐mediated gene expression, and plays key roles in neuronal development, synaptic plasticity and memory. We demonstrated that AAV‐mediated over‐expression of CRTC1 in the dentate gyrus regions of the ventral hippocampus ameliorates the depressive‐like behaviours, the decreased expression levels of brain‐derived neurotrophic factor (BDNF) and VGF, and increased pro‐inflammatory cytokines induced by LPS; knockdown of CRTC1 expression in the hippocampal dentate gyrus regions directly induces depressive‐like behaviours in parallel to down‐regulation of BDNF and VGF expression. This study suggests that CRTC1 is an important mediator of neuroinflammation‐induced depressive‐like behaviour in mice. Read the Editorial Highlight for this article on page 9 . Cover Image for this issue: doi: 10.1111/jnc.14500 .